Pertanggungjawaban Hukum Pidana Terhadap Pelanggaran Rahasia Medis - -, Ridwan (UI Scholars Hub, 2019)
Medical secrets are the patient's rights. This medical secret is a moral obligation based on moral norms derived from Hippocrates' oath. This secret is also known in various professions including advocates, religious scholars and priests, notaries and so on, but the medical profession is the oldest profession that is obliged to keep medical secrets. Maintaining the secret of medicine is an obligation for the medical profession in carrying out its duties and practices as a respect for human dignity. Medical secrets are regulated in international law, especially the law on human rights, Declaration of Human Rights and the 1945 Indonesian Constitution and more specifically in Article 48 of Law Number 29 of 2004 concerning Medical Practices. Medical secrets are not absolute because they can be opened in certain circumstances according to the laws and regulations. If this medical secret is leaked, it can be held to account for the violator, especially Article 322 of the Criminal Code (KUHP).